1998
DOI: 10.3109/10715769809065800
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Against the Involvement of Multiple Radical Generating Sites in the Expression of the Vascular Cell Adhesion Molecule-1

Abstract: The present study was undertaken to investigate the hypothesis that multiple oxygen radical generating systems contribute to the tumor necrosis factor (TNF) alpha-stimulated transcriptional activation of the vascular cell adhesion molecule (VCAM)-1 in endothelial cells. Experimental evidence has implicated the cytochrome P450 monooxygenase and a phagocyte type NADPH-oxidase as a source of oxygen radicals in these cells. We show here that endothelial cells exhibit cytochrome P450 activity by measuring the O-dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…These results are consistent with CYP450-derived ROS, not NADPH-derived oxidants, as essential intermediates in TNF-␣-stimulated expression of MAdCAM-1. With respect to cytokine signaling, our data corroborate and extend findings by Pietersma et al (27), who stated that NADPH oxidase-derived ROS do not appear to contribute to cytokine induction of adhesion molecules in human umbilical vein endothelial cells (HUVEC). Rather, they suggested that cytokine-induced ECAM expression was due to oxidants formed by CYP450 activity.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…These results are consistent with CYP450-derived ROS, not NADPH-derived oxidants, as essential intermediates in TNF-␣-stimulated expression of MAdCAM-1. With respect to cytokine signaling, our data corroborate and extend findings by Pietersma et al (27), who stated that NADPH oxidase-derived ROS do not appear to contribute to cytokine induction of adhesion molecules in human umbilical vein endothelial cells (HUVEC). Rather, they suggested that cytokine-induced ECAM expression was due to oxidants formed by CYP450 activity.…”
Section: Discussionsupporting
confidence: 95%
“…Several prior studies have suggested that a phagocyte-type NADPH oxidase, existing within endothelial cells, might be an important source of signal oxidants (1,12,14,22). Cytochrome P-450 (CYP450) monooxygenases have also recently been proposed as another source of intracellular signaling ROS (8,27,30). Therefore, in the current study we compared the contributions of endothelial NADPH oxidase and CYP450 monooxygenase-derived oxidants in TNF-␣-induced expression of ECAMs.…”
mentioning
confidence: 94%
“…The concentration of H 2 O 2 added to the media of our cell culture experiments (100 μM) may exceed the radical scavenging abilities of this compound, resulting in an inability to prevent the damaging lipid modifications that occur with high levels of oxidants. In addition, previous studies suggest that apocynin’s antioxidant properties are conveyed through inhibiting H 2 O 2 signaling interactions, including cytochrome-P450 (32), thromboxane synthase inhibition (33), the synthesis of the endogenous antioxidant GSH (34), and the inhibition of H 2 O 2 -induced p38 mitogen-activated protein kinase, Akt, and extracellular regulated kinase 1/2 activity (10). Further, our in vivo data demonstrate that apocynin may also serve as an antioxidant in the diaphragm during MV through the maintenance of higher levels of the endogenous antioxidants, GSH and GSH peroxidase.…”
Section: Discussionmentioning
confidence: 99%
“…Apocynin, a methoxy-substituted catechol, blocks phagocytic NADPH oxidase in neutrophils (13,57) and macrophages (40,57) as well as systemic endothelial NADPH oxidase activity (26) through inhibition of p47 phox translocation (39). Other actions include inhibition of thromboxane synthase (13) and cytochrome P450 (48). Additional experiments were performed with diphenyleneiodonium (DPI), which impairs NADPH oxidase by flavoprotein inhibition (15).…”
mentioning
confidence: 99%